Spatial distribution of black carbon emissions in China - Nan Zhang; Qin, Yue; Shaodong Xie (Chinese Science Bulletin, 2013)
Based on the official statistics, locally measured emission factors, and the vehicular emission factor model most suitable for China, we developed a black carbon (BC) emission inventory for 2008 in China and at a spatial resolution of 0.5°×0.5°. In 2008, the total BC emissions in China were 1604.94 Gg. Industry and the residential sector were the dominant contributors, estimated at 695.03 Gg and 636.02 Gg of BC, respectively. Together, these two source types contributed 82.9% of the total emissions. Emissions from transportation were 194.63 Gg, accounting for 12.1% of the total. Since emission contributions from different sectors showed significant spatial diversity among the 31 administrative districts, we divided the districts into four categories: industry contribution district, residential contribution district, industry and residential contribution district, and transportation contribution district. As for energy consumption, coal and biofuel contributed 51.0% and 32.2%, respectively, of the total emissions. Spatially, BC emissions in China were unevenly distributed, higher in the east and lower in the west, corresponding to regional economic development and rural population density. High emission districts, covering 5.7% of the territory, contributed 41.2% of the total emissions. Shanxi, Hebei, Shandong, Henan, and Sichuan were the largest contributors to national BC emissions.